O011/#496 Mirvetuximab soravtansine and bevacizumab in folate receptor αlpha-positive ovarian cancer: efficacy in patients with and without prior bevacizumab. (4th December 2022) - O'Malley, David; Oaknin, Ana; Matulonis, Ursula; Mantia-Smaldone, Gina; Lim, Peter; Castro, Cesar M; Provencher, Diane; Memarzadeh, Sanaz; Method, Michael; Wang, Jiuzhou; Esteves, Brooke; Moore, Kathleen; et al.
Abstract : Objectives: Mirvetuximab soravtansine (MIRV) is a first-in-class ADC comprising a folate receptor-α (FRα)-binding antibody, cleavable linker, and maytansinoid DM4 payload. As part of the phase 1b/2 trial (NCT02606305 ), efficacy, safety, and tolerability of MIRV and bevacizumab (BEV) were evaluated in patients with recurrent FRα-positive ovarian cancer (OC) measured by immunohistochemistry (PS2+ ≥25%). Methods: Patients received MIRV (6 mg/kg, adjusted ideal body weight) and BEV (15 mg/kg) intravenously on Day 1 of a 3-week cycle. Primary endpoint was confirmed ORR assessed by RECIST v1.1. Safety and tolerability of MIRV + BEV were secondary endpoints. Results: Patients enrolled (N=126; median age 62 years) were heavily pretreated (46%, ≥3 prior therapies) and 75% were platinum resistant. Prior taxane, BEV, or PARPi treatment occurred in 98%, 52%, and 27%, respectively. Low, medium, and high FRα expression in patient tumors was 10%, 40%, and 49%, respectively. MIRV demonstrated anti-tumor activity in the entire cohort (ORR 44%, mDOR 11.8 months, mPFS 8.2 months), with ORR of 58% in BEV-naïve and 32% in prior BEV ( table 1 ). Grade 3+ treatment emergent adverse events (TEAEs) were low; common TEAEs (Grade 3+, all grade) included diarrhea (2%, 67%), nausea (2%, 59%), blurred vision (1%, 56%), fatigue (5%, 53%), and hypertension (17%, 33%). Conclusions: MIRV and BEV demonstrated anti-tumor activity, regardless of prior BEV treatment, and should be considered in FRα-positive recurrent OC. A randomized phase 3 trial (GLORIOSA) will evaluate MIRV and BEV in the maintenance setting in patients with FRα-high platinum-sensitive OC.